Painting the volcanic landscape of early Fennoscandia : Geochronology of the Meso- and Neoarchaean Suomussalmi-Kuhmo-Tipasjärvi greenstone complex, Karelia Province, Finland - Lehtonen, Elina (Helsingin yliopisto, 2016)
Archaean cratons contain the oldest parts of the Earth s crust that have survived crustal recycling processes. Archaean greenstone belts are vital parts of these cratons and preserve the oldest volcanoclastic and sedimentary rocks on Earth. They play an important part in the study of the evolution of the early Earth and formation of stable continental crust. One of the most important questions related to Archaean greenstone belts is how they were initially formed. Various tectonic processes have been suggested and the pertinent geological environments remain open for scientific debate. Absolute age determinations of plutonic and supracrustal rocks provide an essential tool for understanding crustal evolution of the early Earth. This thesis focuses on the largest Archae¬an greenstone association in eastern Finland: the Suomussalmi-Kuhmo-Tipasjärvi complex, which belongs to the Karelia Province of the Fennoscandian shield. The main objective of the thesis is to constrain a detailed geochronology for the felsic and intermediate volcanic rocks, as well as sedimentary rocks of the greenstone complex, and associated plutonic rocks. The ages of the selected samples were determined with second¬ary ion mass spectrometry (SIMS) and laser-ab¬lation multi-collector inductively-coupled-mass-spectrometry (LA-MC-ICPMS), and whole-rock samples were analyzed for their major and trace element compositions. The felsic and intermediate volcanic rocks of the Suomussalmi-Kuhmo-Tipasjärvi green¬stone complex can be divided into four distinct age groups based on pre-existing and new geochronological data: 2.94 Ga, 2.84 Ga, 2.82 Ga, and 2.80 2.79 Ga. The Suomussalmi greenstone belt contains the oldest volcanic phase (2.94 Ga), and the Tipasjärvi and Kuhmo greenstone belts the youngest volcanic phase (2.80 2.79 Ga). The new age determinations validate a chronostrati¬graphic interpretation for each belt. The updated chronostratigraphic model of the Suomussalmi greenstone belt comprises four volcanic units: ca. 2.94 Ga (Luoma unit), 2.87 ...